Experimental and Numerical Investigation of the Influence of Process Parameters in Incremental Sheet Metal Forming on Residual Stresses - Maqbool, Fawad; Bambach, Markus (Journal of Manufacturing and Materials Processing, 2019)
The aim of this study is to analyze the co-relation between the geometrical accuracy of parts formed by single-point incremental forming (SPIF) and the resulting distribution of the residual stresses induced in the material as a function of the different process parameters of the SPIF process. The study was performed for a pyramidal frustum manufactured by varying the process parameters of SPIF, i.e., tool diameter, tool step-down, and wall-angle. The hole-drilling strain gage method was used to determine the residual stresses in the manufactured pyramids. Further, small strips were laser cut from the pyramids, and the curvature of the strips was measured. The curvature of the strips is a result of the intensity and distribution of the residual stresses, which in turn depends on the selected values of the process parameters. A validated numerical model of SPIF was used to determine the residual stresses parallel and perpendicular to the direction of tool motion at the center of a strip cut from the numerical model in clamped, unclamped, and trimmed states. Further, the change in the bending moment of a strip that occurred upon unclamping and trimming was calculated. Experimental and numerical investigations reveal that the most significant parameter in residual stress build-up and the reduction of geometrical accuracy is the wall angle. Upon unclamping, the highest change in the residual stresses and bending moment occurred with the largest tool step-down and tool diameter. Upon trimming, the magnitude of the residual stresses and bending moment changed the most with the largest tool step-down in both directions, whereas the change was highest with the smallest tool diameter in the transverse direction of the tool motion. Furthermore, upon trimming, the geometric deviations were highest with the large wall angles in the transverse direction of the tool motion. Overall, the effect of changing process parameters on the residual stress state and geometrical accuracy was more pronounced in the transverse direction of the tool motion.